2016
DOI: 10.1002/jcu.22370
|View full text |Cite
|
Sign up to set email alerts
|

The chorionic bump: Etiologic insights from two pathologic pregnancies

Abstract: The clinical significance and etiology of the chorionic bump remain unclear. We describe two pregnancies characterized by chorionic bumps, which subsequently were diagnosed with a complete mole and trisomy 18, respectively. We hypothesize that placental pathology, including edema and hydropic villi, may contribute to or cause the sonographic finding of some chorionic bumps. An association between chorionic bumps and aneuploidy awaits future study. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:452-454, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…We recently speculated on an alternative etiology for chorionic bumps associated with aneuploidy, suggesting that chorionic bumps observed in some abnormal pregnancies may be the US manifestation of focal or exaggerated placental pathologic features, particularly villus hydrops and stromal edema. 10 The incidence of a chorionic bump was 23/1,000 pregnancies, notably higher than the reported frequency of 1.5-7/1,000. 1,3 The most likely explanation is that the chorionic bump is more prevalent among pregnancies at increased risk for fetal aneuploidy than in the general obstetric population.…”
Section: Discussionmentioning
confidence: 69%
“…We recently speculated on an alternative etiology for chorionic bumps associated with aneuploidy, suggesting that chorionic bumps observed in some abnormal pregnancies may be the US manifestation of focal or exaggerated placental pathologic features, particularly villus hydrops and stromal edema. 10 The incidence of a chorionic bump was 23/1,000 pregnancies, notably higher than the reported frequency of 1.5-7/1,000. 1,3 The most likely explanation is that the chorionic bump is more prevalent among pregnancies at increased risk for fetal aneuploidy than in the general obstetric population.…”
Section: Discussionmentioning
confidence: 69%
“…This is true for the general population as well as for patients with a history of infertility treatment. A computerized search of the Pubmed/MEDLINE database using the term “chorionic bump” revealed six larger series describing between eight to 57 cases and eight isolated reports describing one or two cases. Our report adds an additional 23 cases, for a total of 190 cases reported in the English literature.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and sonographic evidence, as well as an isolated case of magnetic resonance imaging, suggests that this finding probably represents a hematoma . Histopathologic studies are only available in few cases, with two describing a hematoma and another two, a placental edema and gestational tissue . Nevertheless, sonographic appearance and follow‐up information have shown that the chorionic bump usually resolved by the second trimester, with no harm to the fetus, placenta, or chorioamniotic membranes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations